Dragon Harper - McCaffrey, Anne (McCaffrey, Anne. Dragonriders of Pern., 2007)
Life in the Harper Hall is busy for best friends Kindan, Nonala, and Kelsa. As the only female apprentices, Nonala and Kelsa are the butt of jokes and easy targets for the bully Vaxoram and his cronies. But when Kindan springs to Kelsa<U+2019>s defense, he winds up in a fight for his life against the older, bigger Vaxoram<U+2014>a fight that will lead to a surprising friendship. Meanwhile, in nearby Fort Hold, a clutch of fire-lizard eggs is about to hatch, and Lord Bemin<U+2019>s beautiful young daughter, Koriana, is determined to Impress one of the delightful creatures. At the hatching, Kindan Impresses a fire-lizard of his own<U+2026>and wins the heart of Koriana. But Lord Bemin mistrusts harpers and will not hear of a match between his daughter and the low-born Kindan. Then fate intervenes in the form of a virulent plague as fast-spreading as it is deadly. Arising suddenly, as if out of nowhere, the contagion decimates hold after hold, paying no heed to distinctions of birth. In this feverish crucible, friendship and love will be tested to the breaking point and beyond. For with Threadfall scant years away, the Dragonriders dare not expose themselves to infection, and it will fall to Kindan and his fellow apprentices to bravely search for a cure and save humanity. The price of failure is unthinkable. But the price of success may be even harder to bear.